COX1 gene as a promising tool for barcoding different species of Euplotes (Ciliophora: Euplotidae) - Tribun, Mikhail M.; Lebedeva, Natalia A. (Zootaxa, 2026)
Euplotes Ehrenberg, 1830 is a highly diversified genus of ciliates comprising over 160 species. Their identification is problematic at both the morphological and the molecular level. Here, we used an integrative approach to describe four Euplotes species: E. vannus, E. aediculatus, E. sinicus and E. octocarinatus. We obtained 9 new sequences: 4 sequences of the nuclear small-subunit ribosomal RNA gene and 5 sequences of the mitochondrial cytochrome c oxidase 1 (COX1) gene. For two of these species (E. octocarinatus and E. sinicus) the COX1 gene sequences were obtained for the first time. The topology of phylogenetic trees based on the two marker genes was the same for most of the clades. The COX1 gene showed a good resolution at the intraspecific level. This finding indicates that the COX1 gene is a promising tool for barcoding different species of Euplotes.